Gender and conservation agriculture in East and Southern Africa: towards a research agenda. Issue 2 (2nd April 2016) - Farnworth, Cathy Rozel; Baudron, Frédéric; Andersson, Jens A.; Misiko, Michael; Badstue, Lone; Stirling, Clare M.
Abstract : It is remarkable that despite wide-ranging, in-depth studies over many years, almost no conservation agriculture (CA) studies consider gender and gender relations as a potential explanatory factor for (low) adoption rates. This is important because CA demands new ways of working with the farm system. Implementation will inevitably involve a reallocation of men's and women's resources as well as having an impact upon their ability to realize their gender interests. With respect to intra-household decision-making and the distribution of benefits, CA interventions have implications for labour requirements and labour allocation, investment decisions with respect to mechanization and herbicide use, crop choice, and residue management. CA practice may impact upon the ability of households to source a wide variety of crops, wild plants, and insects and small animals for household nutrition. Gender biases in extension service design can sideline women. This paper examines the limited research to date on the interactions between CA interventions and gender in East and Southern Africa, and, based on the gaps observed, sets out a research agenda. It argues that attention to gender in CA is particularly timely given the increasing interest in CA as a means of adapting to climate change.